Self-Determination Theory and Diminished Functioning: The Role of Interpersonal Control and Psychological Need Thwarting - Bartholomew, K.; Ntoumanis, Nikos; Ryan, R.; Bosch, J.; Thøgersen-Ntoumani, Cecilie (Sage Publications, Inc., 2011)
Drawing from self-determination theory, three studies explored the social-environmental conditions that satisfy versus thwart psychological needs and, in turn, affect psychological functioning and well-being or ill-being. In cross-sectional Studies 1 and 2, structural equation modeling analyses supported latent factor models in which need satisfaction was predicted by athletes’ perceptions of autonomy support, and need thwarting was better predicted by coach control. Athletes’ perceptions of need satisfaction predicted positive outcomes associated with sport participation (vitality and positive affect), whereas need thwarting more consistently predicted maladaptive outcomes (disordered eating, burnout, depression, negative affect, and physical symptoms). In addition, athletes’ perceptions of psychological need thwarting were significantly associated with perturbed physiological arousal (elevated levels of secretory immunoglobulin A) prior to training. The final study involved the completion of a diary and supported the relations observed in the cross-sectional studies at a daily level. These findings have important implications for the operationalization and measurement of interpersonal styles and psychological needs.